2019
DOI: 10.1016/j.ijscr.2019.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Lymphaticovenular anastomosis for Klippel-Trenaunay-Weber syndrome

Abstract: Highlights To the best of our knowledge, this is the first report on lymphaticovenular anastomosis (LVA) for the Klippel-Trenaunay-Weber syndrome. We performed seven LVA procedures for the right lower limb with the intention of preventing recurrent bouts of cellulitis. The patient has been cellulitis-free for 1 year post-operatively, having previously had such infection every other month. We suggest that LVA may be effective for the mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Many studies demonstrated the use of LVA for extremity lymphedema treatment, and it is currently the standard lymphedema therapy 6–10 . Furthermore, as we previously reported, groin lymphorrhea, pelvic lymphocele, and chylous ascites caused by lymphatic vessel injuries can also be treated with LVA, as it reduces the amount of lymphatic fluid flowing into injured lymphatic vessels 11 .…”
Section: Discussionmentioning
confidence: 86%
“…Many studies demonstrated the use of LVA for extremity lymphedema treatment, and it is currently the standard lymphedema therapy 6–10 . Furthermore, as we previously reported, groin lymphorrhea, pelvic lymphocele, and chylous ascites caused by lymphatic vessel injuries can also be treated with LVA, as it reduces the amount of lymphatic fluid flowing into injured lymphatic vessels 11 .…”
Section: Discussionmentioning
confidence: 86%
“…20 Lymphaticovenular anastomosis (LVA) has also proven to be effective in the treatment of cellulitis in these patients. 21 Gastrointestinal involvement in KTWS disease is rare but very life-threatening, so in a study by Servelle et al, of 588 KTWS patients, only six had gastrointestinal bleeding and in cases where the patient has severe bleeding, it may be necessary to remove a part of the digestive system. 22 Usually, in KTWS patients, vascular abnormalities do not involve all parts of the digestive system.…”
Section: Discussionmentioning
confidence: 99%
“…There are many ways to remove malformed veins. [7][8][9]15] In this case, due to the man lymphedema of the leg, frequent cellulitis, and skin nutritional disorders, any direct puncture or incision may result in non-healing of the incision or ulceration. Therefore, in the first operation, we performed foam sclerotherapy through the right femoral vein approach into the malformed vein of the left lower extremity.…”
Section: Discussionmentioning
confidence: 99%
“…[5,6] Surgical, endovascular laser or radiofrequency ablation of superficial varicose veins or venous lymphatic anastomosis have been reported to reduce lymphedema, but there is a risk of nonunion of the surgical incision. [7][8][9] In our case, Doppler ultrasonography (DUS)combined with CT venography (CTV) was used to evaluate the clinical and hemodynamic characteristics of KTS, and foam sclerotherapy was applied according to the characteristics of KTS, which successfully prevented frequent cellulitis in the patient with KTS and significantly improved his quality of life.…”
Section: Introductionmentioning
confidence: 99%